Use of adjusted cut-off values for Neospora caninum antibody ELISA in calves after colostrum intake: on-farm evaluation as part of a neosporosis eradication programme - van Velsen CM; Laven LJ; Laven RA; Weston JF (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
Aims: To assess the effectiveness of testing young calves using an ELISA for antibodies to Neospora caninum with adjusted cut-off values to account for the presence of maternal antibodies, as an aid in decision-making during calf-rearing, with the purpose of eradicating neosporosis from endemically infected dairy herds. Methods: Replacement heifer calves on two dairy farms with endemic neosporosis were blood sampled at approximately 1–4 weeks of age. Sera were tested with an ELISA for antibodies to N. caninum, with the thresholds increased (based on unpublished data) to account for colostrum intake. The sample/positive (S/P) cut-off value for seronegative animals was increased from the manufacturer’s recommendation of S/P < 30 to < 70; the S/P value for seropositive was increased from ≥ 40 to ≥ 100; and S/P values 70–100 were considered inconclusive. Calves with inconclusive results were retested using standard thresholds at approximately 4 months of age (after colostral antibodies had waned). Seropositive calves were removed from the replacement herd. This protocol was first implemented in 2016. From 2018 onwards, parentage testing was carried out, and the calves’ results were extrapolated to their dams. Dams of seropositive calves were bred predominantly to beef semen. The proportion of seronegative calves in each cohort from 2016 to 2023 was calculated, and the reproductive performance of seronegative replacement calves (% producing a calf at approximately 24 months of age) was analysed. Results: The proportion of seropositive replacement calves peaked in 2017 (19.5%) and by 2023 had reduced to 1.2%. The odds of a heifer being seronegative in 2023 compared to 2016 were 14.0 (95% CI = 4.12–87.56) times higher. Compared to 2014/2015 when replacement heifers’ serostatus was unknown, after 2016 (the first year when replacement heifer serostatus was established) at least 12.9% more heifers produced a calf at approximately 24 months of age; compared to 2014 the odds were at least 2.88 (95% CI = 1.75–4.88) times higher. Conclusions and clinical relevance: Combining early testing of replacement heifers with the identification and breeding management of dams of seropositive replacement heifers reduced the proportion of seropositive heifer calves in subsequent years and improved the reproductive performance of heifer cohorts. Further research is required to establish optimal ELISA cut-off values, but this strategy is likely to be a useful tool to reduce the N. caninum seroprevalence in endemically infected dairy herds.
Keywords: Neospora caninum; ELISA; control; endemic